Assessment of risk factors for surgical site infection following caesarean section - Sangwan, Aditi; Malhotra, Vani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Assessment of surgical site infection is an important factor to determine the functioning of the health care system. Objectives of this study was to estimate the incidence of surgical site infection among caesarean section cases and to determine the risk factors associated with surgical site infection and comparison with patients having healthy wounds. Methods: One thousand pregnant women who underwent caesarean section were divided into two groups: Group 1 (cases): Those who had SSI within 30 days of caesarean section and Group 2 (controls): Those who didn’t have SSI. Results: Mean age of group I was 25.35±4.40 and 21.12±3.60 years in group II (p >0.05). Mean gestational age of group I cases was 38.07±1.88 weeks and in group II, it was 38.17±2.06 weeks (p >0.05). A total of 37 (82.5%) women in group I and 931 (96.98%) women in group II underwent emergency caesarean section (p <0.05). In group I, mean duration of surgery was 1.0±0.13 hours and 1.02±0.21 hours in group II (p <0.05). Maximum number of patients i.e. 22 (55%) had wound discharge between 4-7 days followed by 11 (27.5%) between 8-10 days. Mean wound discharge was 7.32±3.45 days in group I. Majority of women, i.e. 27 (67%) found to be sterile in the present study followed by 7 (17.5%) women were found to have staphylococcus aureus. Mean duration of resuturing was 17.42±6.98 days. Mean baby weight in group I was 2.72±0.53 kg and in group II it was 2.95±0.53 kg (p <0.001). Conclusions: Risk of developing SSI after caesarean section is multi-factorial and found to be influenced by emergency surgery, PROM, pre-operative anaemia, multiple vaginal examinations, interrupted skin suturing, raised BMI, nulliparity, emergency caesarean, duration of surgery.